Multi-channel surface EMG spatio-temporal image enhancement using multi-scale hessian-based filters - Ullah, Khalil; Khan, Khalil; Amin, Muhammad; Attique, Muhammad; Chung, Tae Sun; Riaz, Rabia (Applied Sciences (Switzerland), 2020)
Surface electromyography (sEMG) signals acquired with linear electrode array are useful in analyzing muscle anatomy and physiology. Most algorithms for signal processing, detection, and estimation require adequate quality of the input signals, however, multi-channel sEMG signals are commonly contaminated due to several noise sources. The sEMG signal needs to be enhanced prior to the digital signal and image processing to achieve the best results. This study is using spatio-temporal images to represent surface EMG signals. The motor unit action potential (MUAP) in these images looks like a linear structure, making certain angles with the x-axis, depending on the conduction velocity of the MU. A multi-scale Hessian-based filter is used to enhance the linear structure, i.e., the MUAP region, and to suppress the background noise. The proposed framework is compared with some of the existing algorithms using synthetic, simulated, and experimental sEMG signals. Results show improved detection accuracy of the motor unit action potential after the proposed enhancement as a preprocessing step.
Keywords: Image enhancement; Multi-scale Hessian-based filter; sEMG; Spatio-temporal image